ANALISIS LEAN HEALTHCARE GUNA MEMINIMASI WASTE PADA POLIKLINIK PENYAKIT ANAK - Fatma Hermining Astuti; Tyan Saskia (JISI: Jurnal Integrasi Sistem Industri, 2021)
Lean Healthcare is an approach to a management system that can change the perspective of a hospital to be more orderly and organized by reducing waste. Waste can be defined as any activity that does not provide  added value  in a process. This study found some waste that occurred in healthcare services at the pediatric clinic of PKU Muhammadiyah Yogyakarta. Value Stream Mapping is used to map the process of services provided to the patients and identify the waste that occurs. A fishbone diagram is used to identify the root cause of waste that has occurred. FMEA is then used to provide recommendations for improvement. The results showed that in the outpatient pediatric polyclinic service process there was waste of 80.7% consisting of waste from production, waiting, transportation, over-processing, inventory, movement and defects. The cause of the critical waste is that the storage space is full, the staff lacks of discipline, doctors often arrive late, patients are lazy to read or look around to find service information, and medical personnel who forget to put data or files. Based on this analysis, some recommendations are provided for improvements: giving training and implementing SOPs, making visual check schedules, implementing safety stock and enforcing discipline with rewards and punishments for medical staff.